Wheat Breeding, Transcription Factories, and Genetic Interactions: New Perspectives - Flavell, Richard B. (Frontiers in Plant Science, 2022)
Epistatic interactions and negative heterosis have been shown to be associated with interchromosomal interactions in wheat. Physical gene-gene interactions between co-regulated genes clustered in “transcription factories” have been documented, and a genome-wide atlas of functionally paired, interacting regulatory elements and genes of wheat recently produced. Integration of these new studies on gene and regulatory element interactions, co-regulation of gene expression in “transcription factories,” and epigenetics generates new perspectives for wheat breeding and trait enhancement.